Islamic Views on Tashwir and its Implications on the Field of Art as a Media of Da’wah - Rizqi, Wahid Tuftazani (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
Islam requires its adherents to preach goodness. The media used are various, one of which is art. As a medium of da'wah, it certainly needs to be considered to what extent it can be used so that it does not violate the provisions of the religion itself. This research is qualitative and focuses on literature. The data collection techniques used are documentation and analysis techniques using descriptive-analytical This study concludes that the field of art in Islam is termed tashwir, which is divided into three legal opinions, namely haram, permissible, and mid. The implication for the use of the arts as a medium of da'wah is that by adhering to opinions that are haraam, art as a medium of da'wah is not permissible. By adhering to the permissible opinion, the arts can be put to good use for the propagation of Islam. Adhering to the median opinion, the use of the arts as a medium of da'wah still takes certain provisions into account